A low-dose biplanar X-ray imager has RSA level precision in total knee arthroplasty. - HURRY, Jennifer K.; SPURWAY, Alan J.; LAENDE, Elise K.; REHAN, Saad; ASTEPHEN WILSON, Janie L.; DUNBAR, Michael J.; EL-HAWARY, Ron (Acta Orthopaedica, 2023)
Background and purpose -- The low radiation biplanar X-ray imager (EOS imaging, Paris, France) scans patients in a weight-bearing position, provides calibrated images, and limits radiation, an asset for serial radiostereometric analysis (RSA) studies. RSA in vivo precision values have not been published for this type of imaging system, thus the goal of this study was to assess the precision of RSA in vivo utilizing a low radiation biplanar imager. Patients and methods -- At a mean of 5 years post-surgery (range 1.4-7.5 years), 15 total knee arthroplasty (TKA) participants (mean age 67 years at the time of imaging, 12 female, 3 male) with RSA markers implanted during index surgery were scanned twice at the same visit in the EOS imager. Precision of marker-based analysis was calculated by comparing the position of the implant relative to the underlying bone between the 2 examinations. Results -- The 95% limit of precision was 0.11, 0.04, and 0.15 mm along the x, y, and z axes, respectively and 0.15°, 0.20°, and 0.14° around the same axes. Conclusion -- This precision study has shown an in vivo RSA precision of ≤ 0.15 mm and ≤ 0.20°, well within published uniplanar values for conventional arthroplasty RSA, with the added benefit of weight-bearing imaging, a lower radiation dose, and without the need for a reference object during the scan.